ANALISIS ISI UNSUR KEBUDAYAAN LOKAL DAN NASIONAL DALAM BUKU AJAR BIPA SAHABATKU INDONESIA B1 - Suryadi, Sopinatul; Rizka Aulia Insani; Anisa Ulfiani; Sindi Karina Sari; Santika; Nuril Indana Ramadani; Baiq Rismariny Nursaly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian for Foreign Speakers (BIPA) learning focuses not only on linguistic proficiency but also on developing pragmatic competence and intercultural awareness. This study aims to analyze the distribution, manifestations, and integration of local and national cultural elements contained in the